2013
DOI: 10.1039/c3nr00500c
|View full text |Cite
|
Sign up to set email alerts
|

Microwave dielectric heating of non-aqueous droplets in a microfluidic device for nanoparticle synthesis

Abstract: We describe a microfluidic device with an integrated microwave heater specifically designed to dielectrically heat non-aqueous droplets using time-varying electrical fields with the frequency range between 700 and 900 MHz. The precise control of frequency, power, temperature and duration of the applied field opens up new vistas for experiments not attainable by conventional microwave heating. We 10 use a non-contact temperature measurement system based on fluorescence to directly determine the temperature insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 47 publications
(101 reference statements)
0
24
0
Order By: Relevance
“…I) TEM image of agglomerated WO 3 nanoparticles, II) diagram of microfluidic flow focusing reactor integrated with a microwave heater (adapted with permission. [108] Copyright 2013, Royal Society of Chemistry) D) Oxide nanoparticles synthesized using an ionic liquid-assisted technique in a microfluidic reactor. I) diagram of the microfluidic reactor, II) TEM image of a ZSM-5 nanoparticle, III) TEM image of β-FeOOH nanorods (adapted with permission.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…I) TEM image of agglomerated WO 3 nanoparticles, II) diagram of microfluidic flow focusing reactor integrated with a microwave heater (adapted with permission. [108] Copyright 2013, Royal Society of Chemistry) D) Oxide nanoparticles synthesized using an ionic liquid-assisted technique in a microfluidic reactor. I) diagram of the microfluidic reactor, II) TEM image of a ZSM-5 nanoparticle, III) TEM image of β-FeOOH nanorods (adapted with permission.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…This renders microwave synthesis a crucial option for well-defined particle fabrication in nanoscience and technology (Hilaire et al, 2014). However, little is still known about the growth mechanisms of metal oxides under the influence of microwaves (Moura et al, 2010;Koziej et al, 2013;Zeng et al, 2013). Therefore, we here provide a broader insight into the crucial influence of a set of different synthesis parameters.…”
Section: Introductionmentioning
confidence: 97%
“…The nonaqueous sol-gel method to the best of our knowledge has only in one report been described to be carried out in a microfluidic system. Koziej et al (Koziej et al, 2013) synthesized tungsten oxide nanoparticles while heating the reaction mixture with a microwave device and investigated the temperature evolution in the droplets with in situ IR-spectroscopy. Koziej et al showed that fast-heated droplets bearing a homogeneous temperature result in homogenous formation and growth conditions, achieving rather uniform and crystalline particles.…”
Section: Introductionmentioning
confidence: 99%